Addressing challenges associated with long‐term topical treatment and benefits of proactive management in patients with psoriasis. Issue Volume 35:Issue S1(2021)Supplement (23rd February 2021) - Lebwohl, M.; Thaçi, D.; Warren, R.B.
Abstract: The majority of patients with psoriasis vulgaris (chronic plaque psoriasis) can be treated successfully with short‐term topical therapies. However, long‐term management of psoriasis with topicals is challenging and tends to take a reactive approach to disease relapse, rather than a proactive approach aimed at maintaining disease remission. Patients are often dissatisfied with the delay in treatment response and inconvenience of applying topical treatments, and therefore frequently discontinue treatment leading to poor outcomes. Relapse is common, particularly with reactive management, as underlying residual disease can remain following initial skin clearance; some patients find that their disease at relapse may be worse than their initial symptoms. This can have a detrimental effect on patient quality of life (QoL) and increase the risk of psoriasis‐associated depression. A long‐term proactive management approach, with maintenance treatment following initial treatment success, could help sustain disease remission and improve clinical and QoL outcomes for patients. Treatment with fixed‐dose calcipotriol 50 µg/g betamethasone dipropionate 0.5 mg/g cutaneous foam (Cal/BD foam) is effective in the short term, providing a fast onset of action and improvements in disease at 4 weeks. Results from the Phase III PSO‐LONG study demonstrated that long‐term proactive management was superior to reactive management in prolonging time to first relapse, reducing number of relapses and increasing days in remission in adults with psoriasis vulgaris. Furthermore, Cal/BD foam was well tolerated in PSO‐LONG. No new safety concerns were identified over 52 weeks; the safety profile was consistent with that described previously. Given this, Cal/BD foam should be considered when prescribing topicals for the long‐term proactive management for patients with psoriasis. Abstract : Video abstract